Modelling the effect of the tidal cycle on the high phytoplankton biomass area of Cape Trafalgar (SW Iberian Peninsula) - Sala, Iria; Vallina, Sergio; Lévy, Marina; Bolado-Penagos, Marina; García, Carlos; Echevarría, Fidel; Sánchez-Garrido, José Carlos (Elsevier, 2023)
Physical–biological interactions in the ocean are known to be crucial for understanding ecosystem processes. In this study, we examine the influence of the tide-topography interaction on the high productivity area of Cape Trafalgar using a high-resolution ocean circulation model coupled to an ecosystem model. The obtained results highlight the relevance of the tidal cycle explaining the high phytoplankton biomass that characterises this region through an active and periodic forcing, resulting in a pulsating upwelling system. Our model shows that the interaction of the westward zonal component of the tidal current (uvel) with the submarine ridge that characterises this region, which is perpendicular to the coast, results in the pumping of deep, cold, salty, and nutrient-rich waters to the well-illuminated subsurface waters, fuelling phytoplankton growth. At the same time, the interaction of the westward tidal current with the ridge leads to the development of a cyclonic eddy, which enables the redistribution of the upwelled waters over and to the east of Barbate High. The fortnightly tidal period has been identified as the most influential because (an effective) tidal-pumping process only takes place when the westward uvel is ∼ 0.42 m s−1, a condition attained between ∼ 3 days before and after the moment of maximum tidal flow during spring tides. Simultaneously, the energy and the associated horizontal and vertical mixing of the cyclonic gyre also vary with the tidal cycle, being stronger during spring tides. Both tidally driven processes, i.e., the cyclical upslope advection of deep nutrient-rich water and the influence of the cyclonic gyre, are the main mechanisms that lead to the development of a persistent phytoplankton-rich tongue over Barbate High. Consequently, Cape Trafalgar acts as a source of nutrient- and phytoplankton-rich waters to the surrounding waters.
Keywords: Mareas - Gibraltar (Estrecho); Fitoplancton marino - Gibraltar (Estrecho); Oceanografía biológica - Gibraltar (Estrecho); Physical–biological interactions; Phytoplankton; Cape Trafalgar; Strait of Gibraltar; Ocean modeling